Mechanical properties of high volume palm oil waste lightweight aggregate concrete containing palm oil fuel ash - Muthusamy, Khairunisa B.; Syed-Mohsin, Sharifah Maszura Binti; Nurfarhayu, Ariffin; Yahaya, F. M.; Jokhio, Gul Ahmed; Kusbiantoro, Andri (2018)
In Malaysia, the abundance of palm oil waste namely palm oil clinker (POC) and palm oil fuel ash (POFA) keep on generated due to high palm oil demand. These two types of waste are usually dumped at the nearby landfill which causes environmental pollution. It is seen that the use of these two types of palm oil waste materials would release some of the total amount of waste landed in the landfill. This research was conducted to investigate the mechanical and durability performance of palm oil clinker lightweight aggregate concrete containing palm oil fuel ash as partial cement replacement. Five types of POC mixes were prepared consisting of 0%, 10%, 20%, 30% and 40% POFA as partial cement replacement. Two types of curing were employed that is water curing and air curing. The finding shows that selection of suitable type of curing and amount of POFA used would contribute towards concrete strength enhancement. Application of water curing with 10% of POFA as partial cement replacement resulted in the highest strength and higher than plain OPS LWAC due to pozzolanic reaction. Continuous presence of water during curing period has facilitate the on better reaction for production of C-SH gel which important for better strength of concrete. On the other hand, air cured specimen exhibit lower strength value at all curing age. The water absorption test result water cured specimen exhibit lower percentage of water absorbed. When exposed to acid resistance test and sulphate resistance test, water cured POC LWAC with POFA shows higher durability than control specimen. Inclusion of suitable amount 10% POFA as partial cement replacement reduces the vulnerable calcium hydroxide owing to pozzolanic reaction that consume it during the production of secondary C-S-H gel. Conclusively, integration of 10% POFA as partial cement replacement enhances both mechanical and durability properties of POW LWAC.